(untitled) (Circe de clásicos y modernos, 2021)
The study of emotions in Antiquity has burst in the last decades. In its development, the Aristotelian systematization of affections (πάθη) (“Book II” of his Rhetoric) has received special attention. In this context, it has been noticed that the emotion of ‘indignation’, as it is defined by the Stagirite (a painful feeling produced by the perception of undeserved prosperity, Rhetoric 1387a8-9) would not have been named by the Greeks as he did it (τὸ νεμεσᾶν). The objection is founded, above all, on the testimonies of forensic speeches (4th century BC). Our proposal incorporates the testimony of Aristophanic comedy into the discussion, since indignation has been considered by many (Cooper, Golden, rosenbloom, among others) the typical emotion of comedy.